PENGARUH MODEL PEMBELAJARAN INKUIRI BERSTRATEGI REACT TERHADAP HASIL BELAJAR KIMIA SISWA SMA KELAS XI (Universitas Negeri Semarang, 2013)
This study aimed to determine the effect of inquiry learning model with REACT strategy on learning outcomes and to determine the contribution to the learning outcomes. The expected benefits are improvements in learning chemistry subjects in class XI of high school through constructivism learning activities. The population in this study were students of class XI of high school in Semarang. The analysis showed the early stages of the population have the same degree of homogeneity and normal distribution. Average learning outcomes after experimental class treated were better than the control class, which amounted to 75.52 and 67.14. Test the difference between two average results obtained t from calculation (4.85) t from table (1.66), so we can conclude the experimental class learning results are better than the control class. Correlation test resulted biserial correlation coefficient (rb) of 0.58 and t from calculation (5.68) t from table (1.99), so the influence was significant. Effect of application of inquiry learning model with REACT strategy shown by the coefficient of determination of 33.64%.The cognitive learning outcomes of experimental class had reached mastery learning classical while control class not yet. The average value of affective and psychomotor experimental classes are better than the control class. Based on these results, it can be concluded that the inquiry learning with REACT strategy have positive effect on learning outcomes chemistry in student class XI of high school in Semarang.